Actor Network Centrality in the Discourse on SUGBK Grass on Social Media X Using Social Network Analysis (SNA) - Ibrahim Nirwanpatra (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study explores the structure of public discourse on the condition of the Gelora Bung Karno Main Stadium (SUGBK) grass field on social media platform X (Twitter) using a Social Network Analysis (SNA) approach. The discourse emerged amid growing controversy involving players, government officials, and the public concerning the field's quality during international football matches. Data were collected through web scraping for the period of January 1, 2024, to January 31, 2025, resulting in 5,011 tweets. The analysis was conducted using Gephi to identify central actors, network patterns, and community modularity. The results indicate a scale-free network structure, where a few dominant nodes such as @idextratime, @CoachJustinL, and @erickthohir served as key Online Opinion Leaders (OOL), showing high scores across degree, betweenness, closeness, and eigenvector centrality metrics. Furthermore, the discourse network revealed significant fragmentation, with over a thousand modularity classes, reflecting a highly participatory yet polarized digital conversation landscape. These findings highlight that influence within digital public discourse is not solely held by formal institutions, but also by grassroots actors who occupy strategic network positions. This study underscores the importance of collaborative engagement between public institutions and influential network actors to better manage digital narratives and promote constructive public engagement.